2013
DOI: 10.1063/1.4794852
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrogen on interstitial iron concentration in multicrystalline silicon during annealing steps

Abstract: The influence of in-diffusing atomic H into an annealed multicrystalline silicon (mc-Si) wafer on the concentration of interstitial iron [Fe i ] was investigated. Neighboring wafers with similar initial [Fe i ] were annealed with and without in-diffusing H. In-diffusion was realized by exposing the samples to a microwave induced remote hydrogen plasma at 400 C. [Fe i ] was detected based on lifetime measurements before and after dissociating the FeB complex. Surface passivation was achieved by a quinhydrone-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 29 publications
4
36
2
Order By: Relevance
“…They suggest that hydrogenation enhances the diffusivity of the bulk iron [17]. A similar finding is reported by Karzel et al [16]. However, a study was not performed on samples from different height positions in an ingot, which is important as the microstructures (particularly dislocation densities) vary significantly [15].…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…They suggest that hydrogenation enhances the diffusivity of the bulk iron [17]. A similar finding is reported by Karzel et al [16]. However, a study was not performed on samples from different height positions in an ingot, which is important as the microstructures (particularly dislocation densities) vary significantly [15].…”
Section: Introductionsupporting
confidence: 64%
“…Recent studies by Liu et al [17], Karzel et al [16] and Leonard et al [30] provide evidence for hydrogen interacting with bulk iron. Our working assumption is that the hydrogen in Set I samples stabilizes bulk lifetime upon annealing at 400 °C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have suggested that the reduction was due to the accelerated precipitation of iron driven by hydrogenenhanced iron diffusivity. 18 However, this hypothesis cannot explain the observed iron loss at higher annealing temperatures, at which the iron solubility limits were well above the dissolved iron concentrations in silicon, meaning that such an iron relaxation precipitation process should not proceed.…”
Section: Introductionmentioning
confidence: 83%
“…[13][14][15][16][17] The mechanism for this iron reduction has remained unresolved, and it has been hypothesised that it might be caused by the hydrogenation of iron in silicon. [13][14][15][16][17] This hypothesis was based on the reports that showed that the recombination activity and the concentration of interstitial iron in silicon were reduced after hydrogen incorporation, via exposure to hydrogen plasma, [18][19][20] hydrogen ion implantation, 21 wet chemical etching, 22 or deposition of PECVD silicon nitride films. 23 While there have been reports of the detection of new defect levels assigned to possible Fe-H complexes, [21][22][23] from theoretical calculations the binding energy of Fe-H pairs was found to be weak, 24 indicating the unlikelihood of the Fe-H pairs withstanding the relatively high temperatures used for firing.…”
Section: Introductionmentioning
confidence: 99%